To evaluate the performance of simultaneous amplification and testing assay for group B Streptococcus detection: comparison with real-time PCR and ddPCR assays - Loukaiyi Lu; Yisheng Chen; Qiang Wang; Jing Gao; Chunmei Ying (BMC, 2024)
Abstract Background To evaluate the performance of simultaneous amplification and testing (SAT) assay for the detection of group B Streptococcus (GBS) in maternal vaginal and perianal swabs compared with real-time polymerase chain reaction (RT-PCR). Methods We obtained vaginal and perianal swabs from 1474 pregnant women at the Obstetrics and Gynecology Hospital of Fudan University (Shanghai, China) between April 2023 and June 2023. Vaginal and perianal swabs were collected at 35-37 weeks of gestation. Swabs were tested for GBS simultaneously by using the SAT assay and RT-PCR, and a comparative analysis (kappa coefficient) was performed. Furthermore, we conducted additional droplet digital PCR (ddPCR) tests to confirm the results when there were controversial results between SAT and RT-PCR. In addition, we compared the limit of detection, technical specificity, repeatability and reproducibility of SAT-GBS with those of routine RT-PCR assays. Results In our study, the detection rate of clinical GBS according to the SAT assay was 11.5% (169/1471). The SAT assay showed a sensitivity of 91.8%, a specificity of 99.9%, a diagnostic accuracy of 98.9%, a positive predictive value (PPV) of 99.4% and a negative predictive value (NPV) of 98.8%. The kappa value between RT-PCR and SAT was 0.917. Conclusions This SAT assay for the detection of group B Streptococcus is not only easy to perform but can also detect GBS sensitively and specifically and may be used in the regular molecular diagnosis of GBS infection among pregnancies.